2023
DOI: 10.1039/d3gc00837a
|View full text |Cite
|
Sign up to set email alerts
|

Versatile electrooxidative amino- and oxyselenation of alkenes

Abstract: Herein, we describe a general and eco-friendly electrochemical methodology for amino- and oxyselenation of alkenes under transition-metal catalyst- and additional-oxidant-free conditions. This electrocatalytic difunctionalisation reaction exhibits excellent chemoselectivity, ample substrate...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 67 publications
(71 reference statements)
0
6
0
Order By: Relevance
“…This is largely due to the inherent challenges of chemoselectivity and regioselectivity issues as well as amine oxidation. Despite these challenges, significant progress has been made (often within restricted substrate classes), 7 a ,8 b ,27 in the areas of three-component alkene selenoamination. During the preparation of this manuscript, Wang, Yi and Hong et al reported a Ca(NTf 2 ) 2 -catalyzed intermolecular selenoamination of alkenes with N -PSP.…”
Section: Resultsmentioning
confidence: 99%
“…This is largely due to the inherent challenges of chemoselectivity and regioselectivity issues as well as amine oxidation. Despite these challenges, significant progress has been made (often within restricted substrate classes), 7 a ,8 b ,27 in the areas of three-component alkene selenoamination. During the preparation of this manuscript, Wang, Yi and Hong et al reported a Ca(NTf 2 ) 2 -catalyzed intermolecular selenoamination of alkenes with N -PSP.…”
Section: Resultsmentioning
confidence: 99%
“…Very recently, the Liu group realized the electrooxidative aminoselenation of alkenes with saccharin and diselenides (Scheme 4). 25 The reaction took place in an undivided cell with C(+)/Ni(−) electrodes and constant current electrolysis at 10 mA with Et 4 NBr as the electrolyte in CH 3 CN at room temperature for 2 h. This method exhibits an advantage over the previously reported aminoselenation of alkenes in a broader substrate scope involving challenging 1-aryl-1,3-dienes ( 4.5–4.8 ) and non-activated aliphatic alkenes ( 4.9–4.11 ). The lower yields obtained with other amine sources resulted from their relatively poor nucleophilic ability under the current electrochemical conditions ( 4.12–4.14 ).…”
Section: Intermolecular Selenofunctionalizationmentioning
confidence: 99%
“…Nowadays, electrochemical synthetic strategies have attracted widespread attentions and present the excellent prospect and potential of difunctionalization of alkenes, including the formation of new chemical bonds such as C–O, , C–S, ,, C–C, , C–N, ,, and C–Se ,, bonds. In these strategies electrons could interact with substrates directly at the anode or cathode, thereby avoiding the demand for metal catalysts or exogenous oxidants .…”
Section: Introductionmentioning
confidence: 99%